Integration Journey of South Asian Professional Migrants into the Finnish Labour Market - Usuf, Abu (My University, 2025)
The globalisation of the labour market, perception of boundaryless careers, demographic changes in the host country, and increasing international competition for specialised talent have driven the global mobility of highly skilled professionals. Finland, facing significant talent shortages in technology, engineering, and scientific disciplines alongside rapid population ageing, has become increasingly dependent on international recruitment. In recent years, migration flows from South Asia have grown substantially. Despite national efforts to attract global talent, many highly educated migrants in Finland face difficulties securing employment commensurate with their qualifications, and a considerable number ultimately leave the country. Existing research on migrant labour-market integration mainly focuses on English-speaking liberal labour-market environments and frequently examines refugees, low-skilled workers, or international students. Researchers often depend on single frameworks that do not fully capture the complexity of integration. Little is known about how highly skilled professionals from culturally distant regions navigate Finland’s institutional frameworks, workplace expectations, and social norms. To fill this gap, the study aims to understand how South Asian professional migrants experience and manage their integration into the Finnish labour market. It explores two key questions: (1) What challenges do South Asian professional migrants face when integrating into the Finnish labour market? and (2) How do they overcome these challenges? To gain a comprehensive understanding of their integration journey, the study adopts a multi-theoretical approach involving Human Capital, Social Capital, and Cultural Intelligence Theory. An exploratory qualitative method was used, including nine semi-structured interviews with South Asian professionals from various sectors, predominantly within Finnish-based multinational companies. Thematic analysis revealed key patterns in participants’ experiences. The analysis identifies three interconnected categories of challenges: structural, social capital and networking, and adapting to new cultural mindsets. Structural challenges include employers’ preference for local credentials, Finnish language requirements, employers’ preference for cultural fit, and unfamiliar labour-market and organisational practices. Social capital and networking challenges stem from reserved interaction norms, slow and competence-based trust formation, and differing communication and knowledge-sharing practices that hinder migrants’ access to meaningful professional ties. Cross-cultural challenges involve understanding new cultural expectations, adapting to new work and social cultures, and balancing personal identity. Despite these barriers, migrants employ three complementary strategies: strategic adaptation to labour market demand and localisation of their human capital, building and enriching social capital, and cultivating cultural intelligence. They pursue Finnish-recognised education and targeted upskilling, form diverse professional networks, cultivate trust-based relationships, and apply cultural learning and behavioural flexibility to navigate workplace norms. The thesis outlines six key theoretical contributions, including: addressing an empirical gap by examining South Asian professionals; developing a multi-theoretical model through proposing a revised conceptual framework that reflects the cyclical and interconnected nature of integration; broadening Human Capital Theory with the concept of human capital localisation; refining Social Capital Theory by emphasising trust-building and cognitive alignment within culturally specific contexts; and advancing Cultural Intelligence Theory by illustrating how migrants adapt selectively in emotionally regulated cultures. These insights enhance understanding of skilled migration in coordinated market economies and provide practical implications for policymakers, employers, and migrants aiming to improve Finland’s capacity to attract and retain global talent.
Keywords: Labour Market Integration, South Asian Professional Migrants, Human Capital, Social Capital, Cultural Intelligence